2004
DOI: 10.1080/00926230490465118
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility to Resources: Helping Rural Women in Abusive Partner Relationships Become Free from Abuse

Abstract: Women in abusive partner relationships seek useful support from family, friends, and the community but are often unsuccessful. Rural women may be especially at risk because of geographical isolation. It was predicted that having a supportive network with access to resources would enable rural women in abusive partner relationships to become free from abuse. We interviewed rural women in previous abusive partner relationships with respect to past and current abuse, supportive and nonsupportive networks, and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 8 publications
0
40
0
1
Order By: Relevance
“…Whether screening for abuse in an institutional setting or rural home visit; providers have expressed their concerns regarding inadequate knowledge regarding the identification and treatment of women experiencing violence as well as IPV resources a provider has available to offer women identified [30, 31, 35, 36, 38, 40–42]. There are unique barriers experienced by rural providers related to resources such as: law enforcement agencies slow response to reports of abuse due to the distance required to travel to the site of the violence and fewer shelters being available in rural areas [30, 31,41–43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether screening for abuse in an institutional setting or rural home visit; providers have expressed their concerns regarding inadequate knowledge regarding the identification and treatment of women experiencing violence as well as IPV resources a provider has available to offer women identified [30, 31, 35, 36, 38, 40–42]. There are unique barriers experienced by rural providers related to resources such as: law enforcement agencies slow response to reports of abuse due to the distance required to travel to the site of the violence and fewer shelters being available in rural areas [30, 31,41–43].…”
Section: Discussionmentioning
confidence: 99%
“…Rural providers may differ in that many times the provider may know the woman she is helping personally, or may know her abuser. This appears to be more of a concern for rural healthcare providers than those in the urban setting where additional resources are available to help provide the anonymity that abused women prefer [31, 32, 41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…The inverse relationship between abuse and access to resources has been supported cross-sectionally and longitudinally (Bosch & Schumm, 2004;Bybee & Sullivan, 2002Sullivan & Bybee, 1999). For instance, among women recruited from a domestic violence shelter, Sullivan and colleagues found that access to community-based resources (e.g., housing, employment, health care, child care) protected women from future abuse.…”
Section: Resource Constraints In the Lives Of Women With Abusive Partmentioning
confidence: 96%
“…The abuser may unilaterally decide that any newly developed relationships the victim forms must be terminated immediately, and will go to great lengths to ensure that this occurs, further intensifying isolation. Of significant note, the abuser uses a rural setting to isolate his victim from anyone who might influence her decisions to report or who could pose a threat to his sense of control (Bosch & Schumm, 2004).…”
Section: Unique Factors For Rural Abusersmentioning
confidence: 99%